Culture of sensationalism and indigenous language press in Zimbabwe: implications on language development - Mpofu, Phillip; Salawu, Abiodun (Routledge, 2022)
Indigenous language media are active spaces for the development, maintenance and renewal of indigenous languages in Africa. Juxtaposing Kwayedza and uMthunywa tabloids, which publish in Shona and Ndebele languages, alongside mainstream English language press, The Herald and The Chronicle, this study interrogates the implications of sensationalism on the structural and functional development of indigenous languages and the indigenous language press in Zimbabwe. This article is framed within the concepts of language development, diglossia and decolonial theory. This is an evaluative and comparative qualitative inquiry of headlines in 30 issues of uMthunywa and Kwayedza. Using interviews, data was gathered from a conveniently and purposively selected sample comprising of journalists, language and media academics, as well as readers and non-readers of Kwayedza and uMthunywa. The study exposes nuances of the marginalisation, folklorisation and corruption of indigenous languages in the press; and the inadvertent validation of English as the language of the media. However, this study ultimately shows that tabloidisation has ensured the survival of indigenous languages and indigenous language press in the context of the hegemony of English and competition from the English language press in Zimbabwe.